STATUS OF FOOD SAFETY COMPLIANCE AND ASSOCIATED FACTORS AMONG STREET FOOD VENDORS IN CHAU THANH COMMUNE, VINH LONG PROVINCE, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess the status of food safety compliance and to analyze associated factors among street food vendors in Chau Thanh commune, Vinh Long province, in 2025.Subjects and methods: A cross-sectional descriptive study was conducted among 319 street food vendors. Data were collected through face-to-face interviews with vendors combined with direct observation of food safety conditions at the vending sites using a structured checklist. Descriptive statistics and logistic regression analysis were employed for data analysis.Results: 73.1% of street food vendors met the food safety criteria. The proportions of vendors with adequate food safety knowledge and appropriate food safety practices were 63.6% and 67.4%, respectively. Adequate knowledge and correct practices were significantly associated with meeting food safety criteria (p < 0.05), whereas no statistically significant associations were observed with vendors’ sociodemographic characteristics or business-related factors (p > 0.05).Conclusion: Improving vendors’ food safety knowledge and practices is essential to enhance compliance with food safety standards among street food vendors.
Keywords: Food safety, street food vendors, knowledge, practice, Vinh Long.